BIOACTIVE PROFILE OF OROBANCHE CARYOPHYLLACEA EXTRACTS DEPENDING ON THE HOST PLANT AND ENVIRONMENTAL CONDITIONS (Proceedings of the YSU B: Chemical and Biological Sciences, 2024)
The impact on parasitic plants is complex and influenced by a combination of biotic and abiotic factors operating at various spatial and temporal scales. In parasite-host relationships as biotic factors, we consider the various host plants impact parasitic plants in varied ways. Our study examined also the correlation between the bioactive profile of the parasite plant and different environmental conditions. Our results demonstrated a correlation between the total polyphenols and antioxidant activity of water-alcohol solutions extracted from the flowers and stems of Orobanche caryophyllacea (bedstraw broomrape) under varying environmental conditions and host plants: Galium verum and Galium humifusum.
Keywords: Orobanche caryophyllacea; parasite-host relationship; bioactive compounds